Strategy of Production Efficiency and Improving the Quality of Wooden Sofa Legs in the Manufacturing Industry - Rahardja, Untung; Lutfiani, Ninda; Duwi Juliansah, Muhamad Alfi; Aptman, Ethan (Pandawan Sejahtera Indonesia, 2025)
This study relates to the challenges faced by the wood furniture industry, specifically in the production of wooden sofa legs, which encounter issues with production efficiency and product quality. Many small and medium-sized enterprises still rely on manual processes that are time-consuming and result in products with varying quality. This research aims to formulate production efficiency strategies that can improve product quality without compromising costs or quality standards. The method used is a descriptive qualitative approach with a case study of a small furniture industry in Pacitan, East Java, through observations, interviews, and documentation, and data analysis using the Miles and Huberman model. The gap in this research lies in the lack of in-depth studies on the production of wooden sofa legs in the context of small and medium-sized industries in Indonesia, particularly in the application of lean manufacturing principles and quality control. The novelty of this research is the integration of lean manufacturing principles and quality control tailored to the specific conditions of small furniture industries, providing strategic recommendations that are practical for industry players. The results and discussion show that the application of the 5S system and production layout improvements successfully increased efficiency and reduced waste, while the implementation of strict quality control at each stage of production improved product consistency. The study also found that worker training and the application of Standard Operating Procedures (SOPs) significantly improved product quality.